ENSO vs glacial-interglacial-induced changes in the Kuroshio-Oyashio transition zone during the Pleistocene - Jacobi, Lara; Nürnberg, Dirk; Chao, Weng-si; Lembke-Jene, Lester; Tiedemann, Ralf (Frontiers in Marine Science, 2023)
The subarctic front (SAF) in the pelagic North Pacific is the northernmost front of the Kuroshio-Oyashio transition zone separating the subpolar and subtropical gyres and is marked by a strong sea surface temperature gradient. A complex interplay of e.g. variations of currents, the wind system and other forcing mechanisms causes shifts of the SAF’s position on timescales from orbital to interannual. In this study, we present proxy data from the Emperor Seamount chain, which reveal a link between long-term ENSO (El Niño/Southern Oscillation) dynamics in the tropics and shifts of the SAF. Based on sediment core SO264-45-2 from Jimmu Seamount (46°33.792’N, 169°36.072’E) located close to the modern position of the SAF, we reconstruct changes in (sub)surface temperature ((sub)SSTMg/Ca) and δ18Osw-ivc (approximating salinities) via combined Mg/Ca and δ18O analyses of the shallow-dwelling foraminifera Globigerina bulloides and the near-thermocline-dwelling Neogloboquadrina pachyderma, biological productivity (XRF-based Ba/Ti ratios), and terrigenous input via dust (XRF-based Fe). From 600 to 280 ka BP we observe significantly higher SSTMg/Ca than after an abrupt change at 280 ka BP. We assume that during this time warmer water from the Kuroshio-Oyashio transition zone reached the core site, reflecting a shift of the SAF from a position at or even north of our study site prior to 280 ka BP to a position south of our study site after 280 ka BP. We propose that such a northward displacement of the SAF between 600-280 ka BP was induced by sustained La Niña-like conditions, which led to increased transport of tropical ocean heat into the Kuroshio-Oyashio transition zone via the Kuroshio Current. After 280 ka BP, the change to more El Niño-like conditions led to less heat transfer via the Kuroshio Current with the SAF remaining south of the core location. In contrast, our productivity record shows a clear glacial-interglacial pattern that is common in the North Pacific. We assume that this pattern is connected to changes in nutrient supply or utilization, which are not primarily driven by changes of the Kuroshio and Oyashio Currents or the SAF.